ELECTRONIC MODULE (E-MODULE) TEACHING MATERIALS THROUGH GEOGEBRA SOFTWARE FOR MIDDLE SCHOOL ON FLAT-SIDED GEOMETRIC MATERIAL - Suripah, Suripah; Febiola, Indah (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
Current developments are increasing rapidly which has an impact on education. Improving the quality of learning requires teachers and students to understand technology. Teaching materials in the form of electronic modules (e-modules) are one form or influence of technology on the world of education. The aim of this research is to produce e-module teaching materials for mathematics learning assisted by GeoGebra on flat-sided geometric material for class VIII SMP that are valid and practical. The type of research used is development research using the ADDIE model. The instruments used are validation and practical instruments (teacher and student response questionnaires). The research results show that (1) the average assessment of e-modules by material experts is 79.36% in the valid category and the average assessment by media experts is 81.58% in the valid category. (2) The average practicality of the teacher response questionnaire assessment e-module was 90.28% in the very practical category and the student response questionnaire assessment obtained an average of 80.96% in the practical category. Based on these results, it can be concluded that the e-module assisted by the GeoGebra software developed is valid and very practical.